Legislation on Freedom of Information : Trends and Standards - Mendel, Toby (World Bank, Washington, DC, 2012)
Coined at the dawn of the scientific age, Bacon's aphorism has taken on new meaning today, when government agencies have at their disposal massive amounts of information about nearly every aspect of modern life. Striking an appropriate balance between the power of government and of citizens to control it demands widespread access to government-held information. As a result there is growing consensus that the right to information is a crucial element of democratic, accountable, responsive government. Recognition of this right has come swiftly. Just over a decade ago it was guaranteed in only a handful of countries. Now more than 50 countries have freedom of information laws, and 15-20 more are considering them. Moreover, a growing number of intergovernmental bodies-including the World Bank, European Union, and United Nations Development Programme-have such policies.